Enrichment Book of Writing Negotiation Texts Containing Pancasila Student Profiles Elements Critical Reasoning for High School Students - Setyaningrum, Puspita; Subyantoro Subyantoro; Wagiran Wagiran (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2024)
The negotiation writing books that are circulating do not fully support writing and critical reasoning skills. This research aims to outline the needs of book development, develop enrichment book profiles, describe expert assessments, and test the effectiveness of books in a limited way. The content of the Pancasila student profile, the element of critical reasoning, is integrated into the text contained in the enrichment book. This content is used to improve students' competence in writing negotiation texts and critical reasoning. This research is a Research and Development (RnD) research with 6 steps, namely (1) potential and problems, (2) data collection, (3) product design, (4) design validation, (5) design revision, and (6) product testing. The results of the study show that students and educators need enrichment books to write negotiation texts containing profiles of Pancasila students, and elements of critical reasoning. The validation test showed a very good category with an average gain of 98.2. The results of the effectiveness test showed that the enrichment book was proven to be effective in learning to write negotiation texts, as evidenced by the increase in pretest and posttest scores with the results of the t-test sig (2-tailed) 0.01<0.05.